Manpower planning and organizational performance: A study of Anambra State Ministry of Environment, 2018 - 2022 - Anaekwe, Victor Benjamine; Okoye, Nonso Sunday; Okoye, Emmanuel; Ohanyere, Chinelo Patience (PT. Pena Produktif Kreatif, 2025)
This study investigated the impact of manpower planning on organizational performance in Anambra State Ministry of Environment, Awka. The specific objective of the study was to examine the effect of training on organizational effectiveness in the Anambra State Ministry of Environment. In line with the objectives of the study, one research questions and hypotheses were formulated. The study adopted descriptive survey research design. The population of the study comprised 320 senior staff of Anambra State Ministry of Environment, Awka. Primary and secondary sources of data was used. Questionnaire was employed as the instrument of data collection. Frequency tables and percentage were employed in analyzing the research questions while the hypotheses were tested using Chi-square statistical technique. The analysis was done using Statistical Package for Social Sciences (SPSS) version 21. The study confirmed that training improves organizational effectiveness in Anambra State Ministry of Environment, Awka. The study concludes that the importance of strategic manpower planning in achieving organizational goals cannot be overemphasized. By investing in employee development, the authority can improve performance, enhance service delivery, and achieve its objectives more efficiently. The study recommended amongst others that Anambra State Ministry of Environment should invest in regular training programs to enhance employee skills and organizational effectiveness.